Advances in the Characterization of the T-Cell Response to Human Herpesvirus-6 - Hanson, Derek J.; Hill, Joshua A.; Koelle, David M. (Frontiers in Immunology, 2018)
Human herpesvirus 6 is thought to remain clinically latent in most individuals after primary infection and to reactivate to cause disease in persons with severe immunosuppression. In allogeneic hematopoietic stem cell transplant recipients, reactivation of HHV-6 species B is a considerable cause of morbidity and mortality. HHV-6B reactivation is the most frequent cause of infectious meningoencephalitis in this setting and has been associated with a variety of other complications such as graft rejection and acute graft versus host disease. This has inspired efforts to develop HHV-6-targeted immunotherapies. Basic knowledge of HHV-6-specific adaptive immunity is crucial for these endeavors but remains incomplete. Many studies have focused on specific HHV-6 antigens extrapolated from research on human cytomegalovirus, a genetically related betaherpesvirus. Challenges to the study of HHV-6-specific T-cell immunity include the very low frequency of HHV-6-specific memory T cells in chronically infected humans, the large genome size of HHV-6, and the lack of an animal model. This review will focus on emerging techniques and methodological improvements that are beginning to overcome these barriers. Population-prevalent antigens are now becoming clear for the CD4+ T-cell response, while definition and ranking of CD8+ T-cell antigens and epitopes is at an earlier stage. This review will discuss current knowledge of the T-cell response to HHV-6, new research approaches, and translation to clinical practice.